A study of physical activity levels and its correlates among adults: a cross-sectional study - Patil, Chaitanya; Dhoble, Manjusha; Kaware, Alka (International Journal Of Community Medicine And Public Health, 2017)
Background: Three fourth of the world’s death burden is shared by low to middle income countries due to non-communicable diseases. Physical inactivity is one of the important preventable risk factor in non-communicable diseases. It amounts to 4th leading risk factor for global mortality. Hence, this study was conducted to study the physical activity level and its correlates among adult patients attending health training centres in Nagpur. Methods: A cross sectional study was conducted among adult patients attending the health centres of Indira Gandhi Government Medical College. Pregnant women, lactating women, debilitated patients and patients not giving consent were excluded from the study. A preformed and pretested questionnaire was used to conduct the interviews which included socio-demographic variables like age, sex, and educational status. Anthropometric measurements and blood pressure were measured according to the standard guidelines. The physical activity level was calculated using the principles of 1985 FAO/WHO/UNU expert consultation (WHO, 1985). Results: Of 200 study subjects, 59% were having a sedentary lifestyle, 27% were having a moderately active lifestyle and 14% were having a vigorously active lifestyle. A statistically significant increasing trend for sedentary study subjects (p =0.002 with age was found. Those who reported sedentary physical activity levels had 3.42 odds of being hypertensive, 7.44 times odds of being diabetic, 3 times odds of being overweight and 2.41 odds of being obese. The adults in urban areas were having significantly less physical activity levels when compared rural areas. Conclusions: Higher levels of sedentary lifestyle were found in urban areas compared to rural areas. As the age increased the sedentary lifestyle was having a significantly increasing trend. Physical activity was associated with the diabetic status, hypertensive status, and obesity status.